The Effect of Performance Appraisal towards Employee Performance and Employee Satisfaction among Employee at University Hospital X - Mohd Nawi, Nursyazliyana; Ismail, Fadillah (Research in Management of Technology and Business, 2021)
Human Resources Management (HRM) is the process of recruiting, selecting, providing orientation, appraising the performance of employees, and providing benefits to employees. Performance appraisal is one of the core components to get effective employee performance and employee satisfaction in their work to grow in business globalization. It could become the organization’s strategy and objective that can achieve in competitive advantage and analyze the higher-level productivity that can benefit the country, organization, and individuals. Therefore, the purpose of this research is to examine the effect of performance appraisal toward employee performance and employee satisfaction among employees at University Hospital X. The quantitative approach was applied to collect data among 104 employees through an online survey questionnaire at University Hospital X. The results from the analysis revealed that there is no relationship between performance appraisal and employee performance. The findings show that P-value is more than 0.05 because the probability value was 0.087 (p>0.05). However, the results also revealed that there is a positive relationship between performance appraisal and employee satisfaction. The findings show that P-value is less than 0.05 because the probability value was 0.000 (p<0.05). The appropriate of this finding indicates the performance appraisal could affect the employee satisfaction among employees positively. The implication for future research is the employer should give motivation to employees so that it can help the improvement of employee performance and employee satisfaction, other than to raise employees’ effectiveness in the organization.